A prospective randomized multicenter study of Turkish Society of Urooncology comparing two different mechanical bowel preparation methods for radical cystectomy - (:unkn) unknown (ELSEVIER SCIENCE INC, 2013)
Objective: To investigate the outcomes and complication rates of urinary diversion using mechanical bowel preparation (BP) with 3 day conventional and limited BP method through a standard perioperative care plan. Materials and methods: This study was designed as a prospective randomized multicenter trial. All patients were randomized to 2 groups. Patients in standard 3-day BP protocol received diet restriction, oral antibiotics to bowel flora, oral laxatives, and saline enemas over a 3-day period, whereas limited the BP arm received liberal use of liquid diet, sodium phosphate laxative, and self administered enema the day before surgery. All patients received same perioperative treatment protocol. The endpoints for the assessment of outcome were anastomotic leakage, wound infection, wound dehiscence, intraperitoneal abscess, peritonitis, sepsis, ileus, reoperation, and mortality. Bowel function recovery, including time to first bowel movement, time to first oral intake, time to regular oral intake, and length of hospital stay were also assessed. Results: Fifty-six patients in 3-day BP and 56 in limited BP arm were evaluable for the study end points. Postoperatively, 1 patient in limited BP and 2 patients in 3-day BP arm died. There was no statistical difference in any of the variables assessed throughout the study, however, a favorable return of bowel function and time to discharge as well as lower complication rate were observed in limited BP group. Conclusions: Regarding all endpoints, including septic and nonseptic complications, current clinical research offers no evidence to show any advantage of 3-day BP over limited BP. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bladder cancer; Radical cystectomy; Mechanical bowel preparation; Urinary diversion; BLADDER-CANCER; SURGICAL ATLAS; MANAGEMENT; RECOVERY; TIME